Force development of track start motion on the starting block with a back plate in competitive swimming - Takeda, T.; Sakai, S.; Ito, S.; Okuno, K.; Takagi, H.; Tsubakimoto, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Some studies about swimming start conducted force measurement acting on the starting block during a track start (Cavanagh et al. 1975; Benjanuvatra et al. 2004). However, no study measured the forces acting on the staring block by front leg, rear leg and hands during a track start. Information about force development during a track start was useful for understanding kinetic characteristics and a good example for a swim start instruction. The purpose of this study was to clarify an application of force by a front-leg, a rear-leg and both hands on the starting block. Methods: Twelve male competitive swimmers participated in this study. They performed a track start from the starting block with a back plate. Two force plates (9258B11 Kistler Inc, TF-2050-W Tecgihan Inc.) were mounted in the starting block to measure force development by front and rear legs separately during a track start motion. The metallic cylinder bar with two built in two load cells (TL3B04 Tecgihan Inc.) was used to measure force development by both hands during the motion. Track start motions were filmed using four high speed cameras (100fps). We obtained three dimensional (3D) coordinates of swimmer`s body parts using 3D DLT method and then extracted 2D coordinates for 2D analysis. 5 m and 10 m head passing time were measure by filming using two cameras placed on the underground pool side deck. Results: Changing in horizontal reaction forces showed that peak values appeared in order of by the hands and by the rear-leg, and by the front leg. The amounts of peak horizontal forces by the hands were small. Changing in the vertical reaction forces showed that greater negative force by hands were shown as opposed to the forces by legs. Mean horizontal velocities generated by the front leg, the rear leg and the hands were 0.35±0.14 m/s, 1.18 ± 0.26 m/s and 2.89 ±0.26 m/s, respectively. Mean vertical velocities generated by them were 4.98 ± 0.58 m/s, 3.14 ± 0.28 m/s and -1.58 ± 0.52 m/s, respectively. Discussion: We have tried to measure force application on the starting block with a back plate during a track start motion. Horizontal reaction force by hands was not greater than a value we expected. The force applied by hands was almost vertical direction. Swimmers pulled the bar by the hands inward at the beginning of starting motion, and they did not push the bar backward to gain the horizontal velocity. The front leg force development dominated the generation of horizontal take-off velocity. On the other hand, the front leg force development dominated the generation of vertical take-off velocity.